Design and Cross-Cultural Invariance of the COVID-19 Vaccine Conspiracy Beliefs Scale (COVID-VCBS) in 13 Latin American Countries - Caycho-Rodríguez, Tomás (2022)
“Aims: Over the past 2 years, the vaccine conspiracy beliefs construct has been used in a number of different studies. These publications have assessed the determinants and outcomes of vaccine conspiracy beliefs using, in some cases, pooled data from different countries, and compared the results across these contexts. However, studies often do not consider measurement invariance as a necessary requirement for comparative analyses. Therefore, the aim of this study was to develop and evaluate the crosscultural MI of the COVID-19 Vaccine Conspiracy Beliefs Scale (COVID-VCBS) in 12 Latin American countries. Methods: Confirmatory factor analysis, item response theory analysis and alignment method were applied to test measurement invariance in a large number of groups. Results: The COVID-VCBS showed robust psychometric properties and measurement invariance for both factor loadings and crosstabs. Also, a higher level of acceptance of conspiracy beliefs about vaccines is necessary to respond to higher response categories. Similarly, greater acceptance of conspiracy beliefs about COVID-19 vaccines was related to a lower intention to be vaccinated. Conclusion: The results allow for improved understanding of conspiracy beliefs about COVID-19 vaccines in the countries assessed; furthermore, they provide researchers and practitioners with an invariant measure that they can use in cross-cultural studies in Latin America. However, further studies are needed to test invariance in other countries, with the goal of developing a truly international measure of conspiracy beliefs about COVID-19 vaccines.“